2022
DOI: 10.3389/fpsyt.2022.997541
|View full text |Cite
|
Sign up to set email alerts
|

Resilience mediates the influence of hope, optimism, social support, and stress on anxiety severity among Chinese patients with cervical spondylosis

Abstract: ObjectiveCervical spondylosis (CS) is a potential stressor threatening mental health among affected individuals. This study was to analyze resilience level and associated factors among cervical spondylosis (CS) patients, and to explore the underlying mechanism of anxiety based on resilience-focused psychological variables.MethodsResilience Scale-14 (RS-14), Zung Self-Rating Anxiety Scale (SAS), Herth Hope Index (HHI), Revised Life Orientation Test (LOT-R), Multidimensional Scale of Perceived Social Support (MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 86 publications
0
6
1
Order By: Relevance
“…We hypothesized that targeting resilience and its determinants could help alleviate anxiety severity among this population. Unexpectedly, the SEM results of this study showed that only perceived stress was significantly correlated with anxiety severity among women with abnormal cervical cancer screening results, which was inconsistent with our previous findings regarding patients with cervical spondylosis [ 24 ]. Interventions towards anxiety among this population should be preferentially focused on stress-buffering strategies rather than on those targeting resilience, hope, or social support.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We hypothesized that targeting resilience and its determinants could help alleviate anxiety severity among this population. Unexpectedly, the SEM results of this study showed that only perceived stress was significantly correlated with anxiety severity among women with abnormal cervical cancer screening results, which was inconsistent with our previous findings regarding patients with cervical spondylosis [ 24 ]. Interventions towards anxiety among this population should be preferentially focused on stress-buffering strategies rather than on those targeting resilience, hope, or social support.…”
Section: Discussioncontrasting
confidence: 99%
“…Accumulating evidence confirms that hope is significantly protective for various mental disorders [ 21 , 22 ]. In addition, hope is also protective for individuals’ resilience [ 23 , 24 ]. Stress refers to the experience of distress when confronted with unpleasant threats or stressors and presents as perceived helplessness and a decrease in self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CS is mainly manifested as neck and back pain, limb weakness and difficulty in walking in the affected patients and all these manifestations seriously decrease the quality of life of the affected individuals [ 14 ]. Indeed, long-term CS symptoms have not only brought about physical distress, but also mental affliction, including anxiety and depression [ 15 , 16 ]. In spite of that, overall little attention has been paid to the psychological impact of this disease and related factors, no matter before or after the COVID-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…Resilience refers to an individual’s ability to successfully cope with significant changes, problems, and notable risks (Abbaspoor et al ., 2020). It acts as a protective factor and defense mechanism against distress, cancer-related stressors, and challenges related to treatment, such as emotional and social stressors (Chu et al ., 2022). Therefore, it is closely associated with mental well-being.…”
Section: Introductionmentioning
confidence: 99%